Hubungan Pengetahuan dan Sikap Orang Tua Dengan Tumbuh Kembang Bayi 6-24 Bulan di PMB Pera Tahun 2025 - Tarigan, Era Vazira; Namirah, Aliya; Wau , Indah Febrianti; Hutapea, Dahlia Carnauba; Tumorang , Herlina Br; Nababan, Tiarnida (Journal of Pharmaceutical and Sciences, 2025)
Background: Growth and development are often considered similar as both involve changes in infants. Growth refers to quantitative changes related to physical maturation, such as increases in body size and weight, which are irreversible. In contrast, development refers to qualitative changes involving the maturation of body functions and structures, and this process continues throughout life. Several factors, including parental knowledge and attitudes, significantly influence and are correlated with infant growth and development. Mothers with low levels of knowledge and negative attitudes are at higher risk of experiencing deviations in their infants’ growth and development. Objective: This study aims to identify the correlation between parental knowledge and attitudes toward infant growth and development among mothers at PMB Pera. Methods: This research used a quantitative approach with an observational design and a cross-sectional study method. Data were gathered by distributing questionnaires and interviews involving 30 respondents. The acquired dataset was processed utilizing univariate and bivariate techniques and tested with the Chi-Square test to examine the correlation between variables. Results: Considering the Chi-Square analysis, there was a significant relationship between parental knowledge and infant growth and development, with a p-value of 0.000. Likewise, parental attitudes toward infant growth and development showed a significant relationship, with a p-value of 0.044. These outcomes indicate that the independent variables in this study have a significant correlation with the growth and development of infants aged 6–24 months at PMB Pera.